Implementation of the RIASEC Model Career Guidance Guide through Career Information Services for Junior High School Students - Muh. Fatur Rahman; Muh. Nur Alamsyah; Hanif Firdaus (Bulletin of Social Studies and Community Development, 2024)
Abstract: Junior high school education is an important phase in student development, especially in exploring interests, talents and career choices. Students need appropriate and structured career information to help them make better decisions regarding their future. However, the existing media is often uninteresting or irrelevant, which cannot support students in recognizing various career options. This study aims to implement the RIASEC Model Career Guidance Guide through career information services at SMPN 2 Pallangga. With a descriptive qualitative approach and narrative method, data were collected through direct interviews with counseling teachers and documentation. The research subjects were 10 9th grade students. The results showed that the implementation of career information services with the assistance of counseling teachers as facilitators. The implementation process focuses on four main aspects: service delivery strategies, stages of implementation, RIASEC-based career guidance content, and media utilization in the form of booklets. This implementation has a positive impact on increasing students' understanding of career planning and helping them recognize their interests and talents. The RIASEC-based guide proved to be relevant as an effective medium to support career information services in schools.   Keywords: information services, career guidance, RIASEC model, guide implementation.